Inheritance of Vernalization Requirement in Carrot - Alessandro, Maria Soledad; Galmarini, Claudio Romulo (American Society for Horticultural Science, 2020)
Carrot (Daucus carota L.) is a cool-season vegetable normally classified as a biennial or winter annual species, requiring vernalization to induce flowering. Nevertheless, some cultivars adapted to warmer climates require less vernalization and can be classified as early flowering or annual. The genetic control of this phenotypic difference has not been previously studied in carrot. The authors evaluated F1, F2, and BC1 progenies of an intercross between the early-flowering carrot (‘Criolla INTA’) and a late-flowering biennial carrot. F1 progenies were completely annual. Observed segregation ratios in the F2 and BC1 families were not significantly different from expected segregation ratios under the hypothesis of a single dominant gene conditioning the early-flowering habit. The authors conclude that annual habit is dominant over biennial and is a monogenic character.